(untitled) (Journal of Fiber Bioengineering and Informatics, 2013)
Wool fabrics both in dry and wet state exhibit high thermal insulation and dry touch, but their main disadvantage - felting, caused by exposition of the fabrics to mechanical action under hot-wet state, might limit their generally excellent properties. Therefore, antifelting treatment is often used to avoid the fabric felting. However, when the level of antifelting treatement is exaggerated, thermal comfort properties of wet wool fabrics might get reduced. In the paper, the effect level of various antifelting treatments on thermal comfort properties of wet wool fabrics was studied with the objective, to determine the levels of treatment, allowing the reduction of the felting behaviour and simultaneously maintain the excellent thermal insulation and thermal contact properties of wool fabrics.